2017
DOI: 10.1016/j.jgr.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ginsenoside bioconversion of lactic acid bacteria isolated from kimchi

Abstract: BackgroundPanax ginseng is a physiologically active plant widely used in traditional medicine that is characterized by the presence of ginsenosides. Rb1, a major ginsenoside, is used as the starting material for producing ginsenoside derivatives with enhanced pharmaceutical potentials through chemical, enzymatic, or microbial transformation.MethodsTo investigate the bioconversion of ginsenoside Rb1, we prepared kimchi originated bacterial strains Leuconostoc mensenteroides WiKim19, Pediococcus pentosaceus WiKi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 39 publications
2
26
0
1
Order By: Relevance
“…The gut microbiota has been extensively investigated due to its involvement in the pharmacological activities of PNS 21 , 23 , 24 , 59 , 60 . Our findings showed that the anti-obesity effects of PNS were mediated by the gut microbiota in DIO mice, in accordance with previous clinical studies, which showed the anti-obesity effects of ginsenosides are dependent on the gut microbiota of obese women patients 22 , 61 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota has been extensively investigated due to its involvement in the pharmacological activities of PNS 21 , 23 , 24 , 59 , 60 . Our findings showed that the anti-obesity effects of PNS were mediated by the gut microbiota in DIO mice, in accordance with previous clinical studies, which showed the anti-obesity effects of ginsenosides are dependent on the gut microbiota of obese women patients 22 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…PNS exert lipid-lowering effects by improving the biosynthesis of bile acids from cholesterol and increasing hepatic fatty acid β-oxidation 18 , and its antioxidative and anti-inflammatory effects are involved in its anti-hyperglycemic effects in diabetic mice 19 , 20 . The gut microbiota has important influences based on its activation of metabolites and pharmacological activities 21 , which have been extensively investigated 22 . PNS have low drug permeability 23 , which results in poor intestinal absorption into the human body, and are thus able to come into contact with the gut microflora for a longer time 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial strain and culture. A bacterial strain was previously isolated from kimchi and identified previously 5,8,38,39 . Lactobacillus plantarum wikim18, Leuconostoc lactis WiKim48, Pediococcus pentosaceus WiKim20, Lactobacillus sakei WiKim49, Leuconostoc mesenteroides WiKim19, Weissella confusa WiKim29, and Lactobacillus brevis WiKim47 were used in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…All bacteria were isolated from homemade kimchi and identified by 16 S rDNA sequencing 42 . The identified 16 S rRNA gene sequences were deposited in NCBI GenBank under accession nos.…”
Section: Methodsmentioning
confidence: 99%